Explorative Pharmaceutical Study and Physicochemical evaluation of Shodhana and Marana of Garudapacha- A rare mineral used in Ayurveda - Govinda Sharma; BN Ashokkumar; Gazala Hussain (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Introduction: Garudapacha is an extra-pharmacopeial mineral drug used as an ingredient in a few formulations of Ayurveda. References and use of these formulations are confined to the regional practices of Kerala and Tamil Nadu. It is a white coloured stone resembling chalk. In the previous works, the mineral drug Garudapacha was identified as Magnesite based on its physical characteristics. There are also references on Shodhana (Purification) and Marana (Incineration) of this stone. But, data on pharmaceutical study and physicochemical characterization of Garudapacha Bhasma is lacking. Methods: Samples of Garudapacha were collected from raw drug vendors of Kerala. Shodhana was carried out through Swedana in Kumari Swarasa for 12 hours. Marana was carried out through three experimental trials: Trial I, II followed two variants ofKukkutaputa methods and trial IIIwith Gajaputa method customized based on available references. Results: The temperature of around 650°C was used in Kukkutaputa and repeated five times, but was insufficient to generate bhasma(calx). The Gajaputa method could generate white Bhasma after five Puta satisfying all the classical tests. A temperature of above 900°C for over 2.5 hours was recorded during all the five Gajaputa with maximum temperature ranging from 952.9°C to 956.9°C. The final yield was 31.4% and the prepared Bhasma was a smooth, soft, white-colored fine powder without grittiness. The Bhasma passed through sieve number 120. During physicochemical analysis, loss on drying 0.2%, Total ash 72.34%, acid-insoluble ash 40.66%, water-soluble ash 6.8% and pH of 10.9 were recorded. Conclusion:Garudapacha Marana requires five Gajaputa with a temperature of around 950°C. The data obtained through physicochemical analysis can be considered as preliminary standard.